2020
DOI: 10.1093/jmcb/mjaa023
|View full text |Cite
|
Sign up to set email alerts
|

The protective role of m1A during stress-induced granulation

Abstract: Post-transcriptional methylation of N6- and N1-adenine can effect transcriptome turnover and translation. Furthermore, the regulatory function of N6-methyladenine (m6A) during heat shock has been uncovered, including the enhancement of the phase separation potential of RNAs. In response to acute stress, e.g. heat shock, the orderly sequestration of mRNAs in stress granules (SGs) is considered important to protect transcripts from the irreversible aggregation. Until recently, the role of N1-methyladenine (m1A) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 71 publications
6
43
0
Order By: Relevance
“…[ 69 ] Indeed, in the complex cellular environment, RNA undergoes a number of modifications such as methylation that can influence RNA structures. [ 70,71 ] Despite the increase in single‐stranded regions in vivo , [ 65,66 ] we found that the correlation between amount of double‐stranded regions and number of protein interactions is still conserved in vivo , which further supports the general validity of the trend (Figure S2).…”
Section: Structure‐driven Rna Interactivity Is An Emerging Property Osupporting
confidence: 75%
See 1 more Smart Citation
“…[ 69 ] Indeed, in the complex cellular environment, RNA undergoes a number of modifications such as methylation that can influence RNA structures. [ 70,71 ] Despite the increase in single‐stranded regions in vivo , [ 65,66 ] we found that the correlation between amount of double‐stranded regions and number of protein interactions is still conserved in vivo , which further supports the general validity of the trend (Figure S2).…”
Section: Structure‐driven Rna Interactivity Is An Emerging Property Osupporting
confidence: 75%
“…We discussed the finding that RNA molecules rich in double stranded regions are highly prone to associate with proteins (Figure 2). [ 6 ] Our observations unveil the existence of “feedback loops” (proteins change RNA structure [ 65,70 ] and RNA induces protein assembly [ 30,61 ] ) that regulate cellular events. [ 56,132 ] In addition to protein‐protein and protein‐RNA interactions, [ 108,133 ] the RNA‐RNA network should be better investigated to achieve a full description of the post‐transcriptional layer of regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Following their previous finding that TRMT6 and TRMT61A are greatly enriched on free mRNA in heat-shocked cell lysates ( Alriquet et al., 2019 ), Alriquet et al. (2020) showed that mRNAs containing the m 1 A motif were significantly enriched in SGs ( Figure 1 ).…”
supporting
confidence: 55%
“…Analysing the motif of mRNAs in SGs revealed a significant enrichment of transcripts targeted by TRMT6/61A (considered as an m1A writer) 55,56 . And further, TRMT6/61A knockout impaired granulation in response to heat shock and arsenite stress, which indicates TRMT61A is involved in RNA granulation under stressful conditions 57 (Figure 1).…”
Section: Stress Granules Formationmentioning
confidence: 96%